Сучасний стан та перспективи використання видів берези (Betula L.) у декоративних насадженнях Києва - Parkhomenko, L.I. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2004)
The question on use of Betula L. species today in ornamental plantations of Kyiv is considered. The groups of fisionomical types of main species woody plants in parks are suggested. Perspectives of introducing Betula species use in landscape compositions are discussed.